Polyvinylidene fluoride (PVDF)/Poly (Ether Sulfones) (PES) blend membrane for CO2/ CO4 for gas separation - Qasem, Ramzi; Sunarti, Abd Rahman; Mohd Bijarimi, Mat Piah; Hasan Alhadadi, Waleed Ali Murshed (Penerbit Universiti Malaysia Pahang, 2022)
In this study, a combination of Polyvinylidene fluoride (PVDF) and Poly (ether sulfones) (PES) blend membrane and DMF as solvent component was developed to evaluate the CO2 and CH4 separation performance. The gas permeation test was thereafter conducted on the membrane produced. The separation through a membrane works on the theory of permeation based on permeability and selectivity. These two important values were estimated using a set of analytical functions. The membranes produced was then characterized using scanning electron microscopy (SEM) and the Fourier Transform Infrared Spectroscopy (FTIR). The result obtained revealed that a higher permeability for the CO2 and CH4 gases when the blending ratio of membrane and solvent of PVDF:PES:DMF/ 5:15:80 were applied. Moreover, the selectivity results showed that the use of the blending ratio of PVDF:PES:DMF/ 20:0:80 produce the highest selectivity (1.3086 GPU) while blending ratio of PVDF:PES:DMF/ 10:10:80 exhibited the least selectivity. In addition, the morphological elucidation revealed the presence of pores for every cross-section composite membrane and this aids the permeability properties of the membrane aggregates at different blending ratio. Also, the FTIR results showed nearly similar functional group characteristics.